Adaptabilidade, estabilidade, fixação e raleio de frutos de pessegueiros em condições tropicais - Souza, Filipe Bittencourt Machado de (2016)
The peach tree (Prunus persica) originated in China and is considered a temperate climate species. When introduced to other climatic regions distinct from its origin, it modifies its behavior for overcoming endodormancy, phenology, vegetative structures and production. In this context, one of the main objectives of the breeding programs of this species is obtaining cultivars with low need for cold since it has direct relation with the adaptability of this fruit tree in locations with low accumulation of cold, characteristic of subtropical and tropical regions. The previous knowledge of the edaphoclimatic conditions of the region to which these cultivars will be introduced is of great importance for the success of the productive chain. The first chapter aimed at the influence of management and temperatures in the first phase of fruit development over the final size of the fruits in Clemenson, South Carolina, in humid subtropical climate (Cfa). The second chapter had the intent of evaluating the sprouting adaptability and stability of 22 cultivars introduced in Lavras, Minas Gerais, Brazil, under high-altitude tropical climate (Cwa) in the productive cycles of 2014 and 2015. The third chapter had the objective of analyzing flowering adaptability and stability of 22 cultivars introduced in Lavras, under highaltitude tropical climate (Cwa) in the productive cycles of 2014 and 2015. The forth chapter aimed at quantifying the germination of grains of pollen and fruit fixation of 18 peach tree cultivars under the application of boric acid. A pre-test was conducted to define the treatments with a preliminary phase in which three concentrations of boric acid were applied (400 mg L -1 , 800 mg L -1 and 1200 mg L -1 ), using water as witness. According to the results, the witness and treatment with 400 mg L -1 was defined for the remaining cultivars, given that it presented the best results in relation to the germination of grains of pollen and fruit fixation.